Identity eaudiobook - Peters, Camille (Kingdom Chronicles, 2020)
Anwen's uncanny resemblance to Princess Lavena has been a curse since the moment she entered her service, as the spoiled princess has frequently used it to her advantage by forcing Anwen to switch places with her. But Princess Lavena's latest scheme is her worst—and most dangerous—yet: compelling Anwen to take the princess's place in her marriage to her loathed fiancé, Prince Liam. Bound by an enchanted contract not to reveal the charade, Anwen is forced to go through with the masquerade and endure a marriage to a man who despises the woman he believes her to be. As time goes on, Anwen struggles not only to maintain her identity, but to fight her deepening feelings as she begins to fall in love with her new husband, a man who not only isn't hers to keep, but who has no idea who she really is.